Addressing the Opioid Crisis through an Interdisciplinary Task Force in Cincinnati, Ohio, USA - Neil J MacKinnon; Ellena Privitera (MDPI AG, 2020)
Opioid use has been a topic of concern in recent years in the United States, causing thousands of deaths each year. Ohio is one of the states hit hardest by the epidemic, and its state and local governments have responded with comprehensive health policies. Cincinnati, located in the southwest region of Ohio, is one of the epicenters of the state's opioid crisis. Responding to the needs of their community, the University of Cincinnati (UC) and its affiliate health system, UC Health, have brought together leaders in research, clinical practice, and education to form the UC/UC Health Opioid Task Force. By encouraging interdisciplinary partnerships, the Task Force is pioneering new ways to understand, prevent, and treat opioid use disorder, while preparing the next generation of healthcare professionals. Additionally, collaboration across departments in UC Health has improved access to treatment and recovery resources for hundreds of patients. Leading educational events, supporting local agencies, and participating in government initiatives have further solidified UC and UC Health's role as a stakeholder in this crisis, showcasing how academic health centers are critical to promoting public health.